Legal Assistance for Child Victims of Sexual Violence from an Islamic Legal Perspective in Accordance with Palangka Raya City Regional Regulation Number 1 of 2021 Concerning the Protection of Women and Children Victims of Violence - Nina Agustina; Syarifudin; Maimunah (al-Afkar, Journal For Islamic Studies, 2025)
Child sexual violence is an increasingly disturbing crime issue and a social emergency in Indonesia. This study aims to analyze the legal assistance process for child victims of sexual violence in Palangka Raya City. Using normative legal research methods with a statutory and conceptual approach, this study examines the legal framework for child protection and compares it with field practices. Data was collected through a literature review of various documents, laws, and relevant literature. The results indicate that the legal assistance mechanism for child victims of sexual violence in Palangka Raya City, through Regional Regulation No. 1 of 2021, has demonstrated structured and comprehensive progress, ranging from assessment and cross-agency coordination to trial assistance and post-trial rehabilitation. However, its effectiveness still faces challenges, including limited human resources, suboptimal coordination, and social stigma. Then, according to the perspective of Islamic law, it is necessary to strengthen the maqashid al-syari'ah (hifz an-nafs and hifz al-'irdh) because child sexual violence is a serious crime that must be dealt with firmly and rehabilitated, so that this regulation is in line with the principles of Islamic justice in protecting children as a mandate from Allah SWT.